2013
DOI: 10.1073/pnas.1218145110
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 regulates BMP signaling and epithelial morphogenesis in the ciliary body of the mouse eye

Abstract: The ciliary body (CB) of the mammalian eye is responsible for secreting aqueous humor to maintain intraocular pressure, which is elevated in the eyes of glaucoma patients. It contains a folded two-layered epithelial structure comprising the nonpigmented inner ciliary epithelium (ICE), the pigmented outer ciliary epithelium (OCE), and the underlying stroma. Although the CB has an important function in the eye, its morphogenesis remains poorly studied. In this study, we show that conditional inactivation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
6
38
0
Order By: Relevance
“…The activity of Mart1::Cre in the eye is restricted to the pigmented epithelial cells of the iris, CB, and RPE (Figure S1), thus allowing deletion of Notch1, Notch2, and RBP‐Jκ specifically in these structures. Consistent with a previous report, loss of Notch2 in pigmented epithelial cells resulted in CB aplasia (Zhou et al., ), a phenotype that was recapitulated in RBP‐Jκ ∆/∆ mice (Figure A). Further histological analysis indicated that other pigmented eye structures such as iris and RPE were normal in RBP‐Jκ ∆/∆ mutants (Figure A and Figure S2), indicating that the CB is the only pigmented structure that requires Notch signaling.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The activity of Mart1::Cre in the eye is restricted to the pigmented epithelial cells of the iris, CB, and RPE (Figure S1), thus allowing deletion of Notch1, Notch2, and RBP‐Jκ specifically in these structures. Consistent with a previous report, loss of Notch2 in pigmented epithelial cells resulted in CB aplasia (Zhou et al., ), a phenotype that was recapitulated in RBP‐Jκ ∆/∆ mice (Figure A). Further histological analysis indicated that other pigmented eye structures such as iris and RPE were normal in RBP‐Jκ ∆/∆ mutants (Figure A and Figure S2), indicating that the CB is the only pigmented structure that requires Notch signaling.…”
Section: Resultssupporting
confidence: 92%
“…This revealed a profound increase in actively cycling pigmented epithelial cells (MITF + ) in the CB (Figure E), indicating that the hyperplastic CB results at least in part from hyperproliferation. This is consistent with the growth promoting and oncogenic functions of excessive Notch signaling reported in other tissues (Koch and Radtke, ), and is in accordance with the reduced proliferation observed in Notch2 null CB (Zhou et al., ). Proliferation was also analyzed during development, when patterning and specification of the CB and iris is occurring.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Cloning of ASD mutations in mice has led to identifying ASD genes in humans (Kuo et al, 2012; McKeone et al, 2011). Additionally, many phenotypes characteristic of ASD—ciliary body and trabecular meshwork hypoplasia, peripheral iridocorneal adhesion, buphthalmos, and elevated IOP—have been found in both spontaneous and genetically modified mouse mutants (Chang et al, 2001; Gould et al, 2007; Kroeber et al, 2010; Libby et al, 2003; Mao et al, 2011; Sarode et al, 2014; Smith et al, 2000; Sowden, 2007; Weng et al, 2008; Zhou et al, 2013). Mutations in transcription factors ( PITX2 , FOXC1 , FOXF2 , LMX1B , PAX6 ) are responsible for numerous cases of ASD and PCG (Gould et al, 2004b) and mouse mutants have been used to study the cell biology of these genes in the eye.…”
Section: Glaucoma-relevant Anterior Segment Diseasementioning
confidence: 99%
“…Recent work with mice carrying mutations in various cell-cell signaling components is beginning to give us insight into the inductive events that drive anterior segment development. For instance, BMP4, a secreted molecule belonging to the TGFβ superfamily, is believed to be necessary for proper formation of both the ciliary body and the iridocorneal angle (Chang et al, 2001; Zhou et al, 2013). Additionally, mutations in several genes influencing the extracellular matrix (eg.…”
Section: Glaucoma-relevant Anterior Segment Diseasementioning
confidence: 99%